Feasibility study of an integrated stroke self-management programme: a cluster-randomised controlled trial. Issue 1 (6th January 2016) - Jones, Fiona; Gage, Heather; Drummond, Avril; Bhalla, Ajay; Grant, Robert; Lennon, Sheila; McKevitt, Christopher; Riazi, Afsane; Liston, Matthew
Abstract : Objectives: To test the feasibility of conducting a controlled trial into the effectiveness of a self-management programme integrated into stroke rehabilitation. Design: A feasibility cluster-randomised design was utilised with stroke rehabilitation teams as units of randomisation. Setting: Community-based stroke rehabilitation teams in London. Participants: 78 patients with a diagnosis of stroke requiring community based rehabilitation. Intervention: The intervention consisted of an individualised approach to self-management based on self-efficacy. Clinicians were trained to integrate defined self-management principles into scheduled rehabilitation sessions, supported by a patient-held workbook. Main outcomes measures: Patient measures of quality of life, mood, self-efficacy and functional capacity, and health and social care utilisation, were carried out by blinded assessors at baseline, 6 weeks and 12 weeks. Fidelity and acceptability of the delivery were evaluated by observation and interviews. Results: 4 community stroke rehabilitation teams were recruited, and received a total of 317 stroke referrals over 14 months. Of these, 138 met trial eligibility criteria and 78 participants were finally recruited (56.5%). Demographic and baseline outcome measures were similar between intervention and control arms, with the exception of age. All outcome measures were feasible to use and clinical data at 12 weeks were completed for 66/78 participants (85%; 95% CI 75% to 92%). There was no significant difference in any of the outcomes between the arms of the trial, but measures of functional capacity and self-efficacy showed responsiveness to the intervention. Observation and interview data confirmed acceptability and fidelity of delivery according to predetermined criteria. Costs varied by site. Conclusions: It was feasible to integrate a stroke self-management programme into community rehabilitation, using key principles. Some data were lost to follow-up, but overall results support the need for conducting further research in this area and provide data to support the design of a definitive trial. Trial registration number: ISRCTN42534180.